2016
DOI: 10.7759/cureus.878
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usage and Economic Effectiveness of a Recently Developed Epidermal Autograft Harvesting System in 13 Chronic Wound Patients in a University-Based Wound Center

Abstract: Introduction: Chronic wounds are a significant healthcare problem in the United States. Their costs approach 25 billion dollars in the United States. Current wound-care treatments of local wound care, moist dressings, and source control, while necessary for wound healing, are frequently not enough to ensure complete wound closure. The current surgical technique of split-thickness skin grafting is an operative procedure, painful, time-consuming, and leaves significant donor site wounds. A recently developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Moreover, the AEMH system has been successfully applied in patients with chronic wounds, ulcers of pyoderma gangrenosum, and burns. [18][19][20] Of note, the designated AEMH facilitates the pro- however, several studies have reported potential financial benefits of AEMH in long-term wound care. 20,21 On the contrary, melanocyte-keratinocyte transplant procedure (MKTP) is a cellular grafting technique for treating vitiligo and provides a high recipient-to-donor ratio enabling therapy of large achromic areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the AEMH system has been successfully applied in patients with chronic wounds, ulcers of pyoderma gangrenosum, and burns. [18][19][20] Of note, the designated AEMH facilitates the pro- however, several studies have reported potential financial benefits of AEMH in long-term wound care. 20,21 On the contrary, melanocyte-keratinocyte transplant procedure (MKTP) is a cellular grafting technique for treating vitiligo and provides a high recipient-to-donor ratio enabling therapy of large achromic areas.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Janowska et al 17 reported good to excellent repigmentation response observed in five cases of stable vitiligo receiving AEMH. Moreover, the AEMH system has been successfully applied in patients with chronic wounds, ulcers of pyoderma gangrenosum, and burns 18‐20 . Of note, the designated AEMH facilitates the production of uniform epidermal micrografts under appropriate vacuum and heat conditions; the epidermal microdomes created at the derma‐epidermal junction contain viable basal cells actively secreting wound‐healing growth factors such as vascular endothelial growth factor, platelet‐derived growth factor, hepatocyte growth factor, and granulocyte colony‐stimulating factor, contributing to a favorable environment for further cell migration and proliferation 11 …”
Section: Discussionmentioning
confidence: 99%
“…Although, costs of an Integra ® bilayer wound matrix per unit is substantially higher than an autologous skin graft, these costs may be offset by reduced intraoperative times and equipment required for autograft harvesting, as well as foregone time and resources required for postoperative donor site wound management 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…Although, costs of an Integra ® bilayer wound matrix per unit is substantially higher than an autologous skin graft, these costs may be offset by reduced intraoperative times and equipment required for autograft harvesting, as well as foregone time and resources required for postoperative donor site wound management. 21,22 Split-thickness skin grafts are usually fragile and may easily tear while suturing to adjacent oral mucosa, whereas the silicone layer of the Integra® bilayer wound matrix increases its tear strength and permits easier handling. Furthermore, Integra® skin substitute allows granulation of native fibroblasts into the biodegradable collagen layer and epithelization through secondary intention, which leads to normal epithelialization of the recipient site.…”
Section: Discussionmentioning
confidence: 99%
“…In a different emerging approach of autologous grafting, Epidermal grafting (EG), harvesting of only the epidermal layer is achieved by applying heat to the area to form and raise blisters by negative pressure (Herskovitz, Hughes, Macquhae, Rakosi, & Kirsner, ). Nonetheless, autologous skin grafts can be associated with infection, pain, dyschromia, and hypertrophic scarring, with restrictions toward the total amount of skin that can be harvest from a patient (Hulsey, Linneman, & Litt, ).…”
Section: D Electrospinning For Skin Tissue Engineeringmentioning
confidence: 99%